Characterization of Simulium (Simulium) hackeri Edwards (Diptera: Simuliidae) from Malaysia: Morphological description of the pupa and larva, and DNA barcoding - Ya'cob, Zubaidah; Takaoka, Hiroyuki; Low, Van Lun; Sofian-Azirun, Mohd (Elsevier, 2018)
Simulium (Simulium) hackeri Edwards, 1928 of the Simulium variegatum species-group from Malaysia was described initially based on the female specimen from Cameron Highlands, Pahang. In the present study, the pupa and larva of this species are described for the first time. Their morphological characters resemble those of the Simulium variegatum species-group by having six gill filaments per side, abdomen with dorsal spine-combs at least on segments 7 and 8, cocoon with wall-pocket shaped and with or without an anterodorsal projection. Postgenal cleft of the larva medium-sized, rarely small, ventral papillae small or absent. The DNA barcode of this species is also reported herein.